A comparison of the proportion of early stage cholangiocarcinoma found in an ultrasound-screening program compared to walk-in patients. Issue 6 (June 2020) - Khuntikeo, Narong; Koonmee, Supinda; Sa-Ngiamwibool, Prakasit; Chamadol, Nittaya; Laopaiboon, Vallop; Titapun, Attapol; Yongvanit, Puangrat; Loilome, Watcharin; Namwat, Nisana; Andrews, Ross H.; Petney, Trevor N.; Thinkhamrop, Kavin; et al.
Abstract: Background: Patients with cholangiocarcinoma (CCA) usually have no specific symptoms until an advance stage of the disease and curative treatment is not possible. Patients with early stage, operable disease can be found using ultrasonography (US). A US-screening program was implemented in Thailand where CCA incidence is the highest worldwide. Here we evaluate the effectiveness of the program by comparing the proportion of individuals with early stage CCA in the screening group with that of the walk-in group presenting at hospitals with clinical symptoms. Methods: All patients had a pathological diagnosis of CCA. The difference in the proportions and the 95% confidence interval (CI) were obtained using binomial regression. Results: Of the 762 histologically proven CCA cases, 161 were from the screening group and 601 from the walk-in group. The proportion of early stage CCA (stages 0 to II) diagnosed was 84.5% in the screening and 21.6% in the walk-in groups. After adjustment age, gender, and liver fluke infection, there was a significantly higher proportion ( P  < 0.001) and higher chance ( P  < 0.001) of having early stage CCA in the screening group than in the walk-in group. Conclusions: US-screening is an effective tool for detecting early stage, operable CCA in high incidence areas.